KEMITRAAN PT PASANGKAYU DAN MASYARAKAT DESA AKO MELALUI PROGRAM CSR ASTRA KREATIF DALAM PENGEMBANGAN USAHA AYAM PETELUR - Amanda Amanda; Fadilah Ramadhani; Mohamad Abdul Yulianto; Putri Ganda Lestari; Safika Cindy Maharani; Sugeng Bahagia Hidayanto; Nawawi Natsir; Fiki Ferianto; Nuraisyah Nuraisyah (CV. KAMPUSA AKADEMIK PUBLISING, 2026)
Abstract. This study analyzes the partnership between PT Pasangkayu a subsidiary of PT Astra Agro Lestari, which operates in the oil palm plantation sector in Pasangkayu Regency, West Sulawesi and the Ako Village community within the framework of a Corporate Social Responsibility (CSR) program entitled Astra Kreatif. This program aims to develop laying hen farming as a strategy to strengthen the economic independence of the local community. This study used a descriptive qualitative approach, collecting data through interviews, observations, and document reviews. The results indicate that the program's implementation, which included the provision of 202 laying hens, production equipment, livestock management training, and ongoing technical support, significantly contributed to increased incomes for beneficiary households. Beyond economic benefits, the program also generated positive social impacts, including strengthened community cooperation, increased participation in productive activities, and enhanced women's economic roles within the household. The study concludes that a collaborative partnership model between the private sector and local communities is an effective strategy for promoting sustainable rural development and improving the well-being of the community.